ULTRASONOGRAPHY VERSUS COMPUTED TOMOGRAPHY FOR DETECTION OF UROLITHIASIS - AFZAL , A; AFZAL , U; ASGHAR , R (Biological and Clinical Sciences Research Journal, 2024)
Urolithiasis, or urinary stone disease, is a common condition with potentially severe health implications if undetected or untreated. While computed tomography (CT) is the gold standard for detecting urolithiasis, ultrasonography (USG) is often preferred in clinical practice due to its accessibility, non-invasiveness, and lower cost. Evaluating the diagnostic accuracy of USG compared to CT can help guide its use in diagnosing urolithiasis. Objective: To determine the diagnostic accuracy of ultrasonography in detecting urolithiasis, using computed tomography as the gold standard. Methods: This cross-sectional study included 320 patients suspected of urolithiasis, aged 18-70, who were examined at the Department of Radiology in collaboration with the Department of Urology at Sir Ganga Ram Hospital, Lahore from January 2024 to July 2024. CT scans were conducted using the Toshiba Aquilion TSX-101A/4 slice CT Scanner, while ultrasound imaging was performed with the Toshiba Aplio 500, using a 3.5 MHz curved transducer. Data analysis focused on diagnostic accuracy, sensitivity, and specificity of USG compared to CT. Results: The mean age of the patients was 42.08±15.38 years, with a male predominance of 54.4% (174/320). The average body mass index (BMI) was 24.48±4.57 kg/m², and the mean stone size detected was 18.18±10.86 mm. Ultrasonography demonstrated a sensitivity of 95.8%, specificity of 100%, and overall diagnostic accuracy of 96.5% in detecting urolithiasis when compared to CT. Conclusion: Ultrasonography shows high sensitivity (95.8%) and excellent specificity (100%) in detecting urolithiasis, with an average detected stone size of 18.18±10.86 mm. These findings support the use of USG as a reliable, accessible diagnostic tool for urolithiasis, especially when CT is not readily available.